Implementasi Diferensiasi Pembelajaran untuk Mengatasi Kesenjangan Kemampuan Belajar pada Mata Pelajaran Pendidikan Pancasila di Kelas IV - Wardhani, Ridha Yogie; Putri, Elisa Setia; Widodo, Susilo Tri; Rahayu, Heti Kristining (YASIN, 2025)
Although differentiated instruction has been widely examined in the context of the Kurikulum Merdeka, research that specifically focuses on its application to address disparities in students’ learning abilities in Pendidikan Pancasila at the elementary school level remains limited. This study aims to evaluate the effectiveness of differentiated instructional strategies in improving the learning outcomes of Grade IV students at SDN Protomulyo 2. Using a quantitative approach with a Classroom Action Research (Penelitian Tindakan Kelas, PTK) design based on the Kemmis and McTaggart model, the study was implemented over several cycles comprising planning, implementation, observation, and reflection stages, involving 30 students selected through total sampling. Data were collected through achievement tests and observations of student activities, and were analyzed descriptively to identify changes in learning outcomes and engagement. The results show a substantial improvement in learning outcomes, as evidenced by 66.7% of students achieving the very good category after the intervention. In addition, classroom learning became more active, inclusive, and responsive to individual learning needs in terms of content, process, and product. These findings reinforce the theoretical foundations of differentiation and extend understanding of its application in Pendidikan Pancasila at the elementary level. The study underscores the importance of instructional strategies that are adaptive to diverse student abilities and recommends that schools optimize teacher training in the design and sustainable implementation of differentiated instruction.